In vitro and in silico analysis of potential antioxidant peptides obtained from chicken hydrolysate produced using Alcalase. (July 2022) - Xiao, Chuqiao; Toldrá, Fidel; Zhao, Mouming; Zhou, Feibai; Luo, Donghui; Jia, Ruibo; Mora, Leticia
Graphical abstract: Highlights: Chicken hydrolysates showed antioxidant activity and resisted simulated digestion. 22 peptides were identified by mass spectrometry after activity-oriented separation. Novel peptides RWGG, YYCQ, and KAPKL were predicted in silico to be bioactive and bio-accessible. YYCQ exert the strongest antioxidant activity with TEAC value of 3.54 and 4.28 μM TEAC/μM in ORAC and ABTS assay, respectively. Abstract: Chicken hydrolysates (CHs) have been reported to protect mice against alcoholic liver injury possibly through oxidative stress reduction. In this study, the antioxidant activity of CHs was studied. Results showed that CHs exhibited significant antioxidant activity (around 600 and 400 μM TEAC/g in ORAC and ABTS assay, respectively) and could resist simulated gastrointestinal digestion. A total of 22 peptides were identified after antioxidant activity-oriented isolation using size-exclusion chromatography and high-performance liquid chromatography. Further in silico analysis and the validation of antioxidant activity revealed that novel peptides (RWGG and YYCQ) exhibited strong antioxidant activity. The most active peptide YYCQ displayed a TEAC value of 3.54 and 4.28 μM TEAC/μM in ORAC and ABTS assay, respectively. These peptides could contribute to reduce oxidative stress and protect against alcohol-induced liver injury. However, further studies understanding the bioactivity of such peptides in vivo are necessary before further applying them as functional food ingredient.